P30-T Localizing value of interictal electrical source imaging: Who are the best candidates?. Issue 7 (July 2019) - Koessler, Laurent; Abdallah, Chifaou; Rikir, Estelle; Thiriaux, Anne; Gavaret, Martine; Bartolomei, Fabrice; Colnat-Coulbois, Sophie; Maillard, Louis
Abstract : We aimed to prospectively assess the anatomical concordance of electric source localizations of interictal discharges with the epileptogenic zone (EZ) estimated by stereo-electroencephalography (SEEG) according to different subgroups: the type of epilepsy, the presence of a structural MRI lesion, the aetiology and the depth of the EZ. In a prospective multicentric observational study, we enrolled 85 consecutive patients undergoing pre-surgical SEEG investigation. Electric source imaging (ESI) was performed before SEEG. Anatomical concordance between ESI and EZ was defined according to 36 predefined sublobar regions. ESI was interpreted blinded to- and subsequently compared with SEEG estimated EZ. 74 patients were finally analyzed. 38 patients had temporal and 36 extra-temporal lobe epilepsy. MRI was positive in 52. 41 patients had malformation of cortical development (MCD), 33 had another or an unknown aetiology. EZ was medial in 27, lateral in 13, and medio-lateral in 34. In the overall cohort, ESI completely or partly localized the EZ in 85%: full concordance in 13 cases and partial concordance in 50 cases. The rate of ESI full concordance with EZ was significantly higher in (i) frontal lobe epilepsy (46%; p = 0.05), (ii) cases of negative MRI (36%; p = 0.01) and (iii) MCD (27%; p = 0.03). We demonstrated that ESI more accurately estimated the EZ in subgroups of patients who are often the most difficult cases in epilepsy surgery: frontal lobe epilepsy, negative MRI and the presence of MCD.